THE PHYSICAL ACTIVITY OF TNI-AD WARRIORS IN THE COVID-19 PANDEMIC - Akhmad Sobarna; Sumbara Hambali; Henry Asmara; Aditya Yoga Pratama; Idris Supriadi (Cakrawala Pedagogik, 2022)
The purpose of this study was to determine the level of physical activity of TNI-AD soldiers in the 201/Jaya Yudha Mechanic Yonif Unit during the Covid-19 pandemic. The research method used is a survey method. All TNI-AD Soldiers in the 201 / Jaya Yudha Mechanic Yonif Unit, totaling in 1 company, consisted of 108 people, and the sample was taken using purposive sampling technique, so the sample used was 23 people. The instruments used were a questionnaire about physical activity from Baecke and analysis of BMI (Body Mass Index) with the formula BMI = BW (Kg)/TB (m) 2. The technique of calculating and analyzing data in this research is through a quantitative approach in the form of a percentage. Based on the results of the study, it can be seen that the results of the average physical activity index when exercising get an average value of 3.4 in the fairly active category, mean that physical activity at the time when you get an average value of 3.5 is in the active category, and the results analysis on the Body Mass Index (BMI) of the soldiers scored 24.2 kg / m2, which means that they are in the Normal category.